2020
DOI: 10.1002/jsc.2324
|View full text |Cite
|
Sign up to set email alerts
|

Industrial clusters in the developing economies: Insights from the Iranian carpet industry

Abstract: Industrial clusters are perceived as potential drivers of small and medium‐sized enterprises development and efficient policy instruments to lead national and regional innovation and growth. However, these clusters in developing economies are typically placed in complex environments that impose a mix of serious challenges that adversely affect their overall performance. Therefore, this study aims to analyze the nature of these challenges and understand their dynamics using a case study of a carpet industry clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(20 citation statements)
references
References 56 publications
0
17
0
Order By: Relevance
“…would perceive their working systems as incompatible (Saadatyar et al, 2020). Thus, failure to tackle these differences can seriously undermine the interaction and communication, that underpin collective learning-adaptation endeavor, as partners would lose their relational capital-that is much needed to maintain trust and commitment within the relationship (Luo, 2020).…”
Section: Similarlymentioning
confidence: 99%
See 1 more Smart Citation
“…would perceive their working systems as incompatible (Saadatyar et al, 2020). Thus, failure to tackle these differences can seriously undermine the interaction and communication, that underpin collective learning-adaptation endeavor, as partners would lose their relational capital-that is much needed to maintain trust and commitment within the relationship (Luo, 2020).…”
Section: Similarlymentioning
confidence: 99%
“…In effect, cross-sector collaboration brings together organizations from two sectors or more that are inherently different due to their diverse ideologies, institutional logic, business models, motives, culture and value systems (Selsky and Parker, 2005). These discrepancies can complicate the collaboration process as partners would perceive their working systems as incompatible (Saadatyar et al, 2020). Thus, failure to tackle these differences can seriously undermine the interaction and communication that underpin collective learning-adaptation endeavor, as partners would lose their relational capital that is much needed to maintain trust and commitment within the relationship (Luo, 2020).…”
Section: Casementioning
confidence: 99%
“…Meanwhile, as the literature emphasizes, social capital is a necessary condition to unleash the innovative potentials in clusters and other networks of enterprise connections. Sharing information, knowledge, and ideas requires trust (Hoffman, 2014;Lai et al, 2014;Garcia-Villaverde et al, 2017;Saadatyar, Al-Tabbaa, Dagnino, & Vazife, 2019) and these structures become dysfunctional without this element, leading to failure in meeting expectations or fulfilling tasks. As emphasized by Chen, Haga, and Fong (2016), the lack of social capital means that the cooperation structures created are usually short-lived, because social capital is a kind of "glue" that holds them together.…”
Section: Discussionmentioning
confidence: 99%
“…That is also because the results on the formation and development of effective links within clusters have not been optimistic. It has been firmly identified that the mere creation of a cluster does not release its innovative potential (Saadatyar et al, 2019). To make it happen, it is necessary to reach an openness to establish cooperation with all its actors, including competitors.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation